Isolation and Characterization of Plant Growth Promoting Endophytes from Linum Usitatissimum - Shalu Choudhary; Bhandari, Geeta; Anant Deogaonkar; Deepshree Kumar; Kanishka Miglani; Sanjay Gupta; Samiksha Joshi; Amit Mittal; Gangola, Saurabh (Research in Ecology, 2025)
This present study identifies endophytic bacteria from Linum usitatissimum with multidimensional plant growth-promoting attributes, positioning them as ecological engineers for sustainable agriculture. Plant growth-promoting bacteria (PGPB) are present in symbiotic associations with plants or rhizosphere. These microbes enhance crop productivity and resilience under different environmental conditions. Endophytes are a type of PGPB that inhabit inside plant tissues and contribute to plant growth by phytohormone production, phosphate solubilisation, zinc solubilisation, siderophore production, ammonia production, nitrogen fixation, stress tolerance, and biocontrol mechanisms. Twelve bacterial strains were isolated from Linum usitatissimum exhibiting plant growth-promoting attributes such as ammonia and indole-3-acetic acid (IAA) production, siderophore synthesis, phosphate solubilisation, and extracellular enzyme synthesis. The isolated endophytes were also assessed for different enzymatic activities such as; cellulase, pectinase, xylanase, amylase, and gelatinase, which contribute to development of a symbiotic relationship and are crucial for the degradation of plant cell wall components The most efficient endophytes identified in the present study were Pseudomonas sp. strain JL-1 (ESL1) and Staphylococcus sciuri (ESL2), both of which displayed strong plant growth-promoting potential. ESL1 and ESL2 demonstrated promising plant growth-promoting characteristics and cellulase, pectinase, xylanase, amylase, and gelatinase, activity. ESL2 (Staphylococcus sciuri) enhanced nutrient cycling (phosphate solubilisation: 196–209 µg/ml; siderophores: 68–71%) and stress tolerance (IAA: 11–12 µg/ml), reducing reliance on synthetic inputs. By integrating flax microbiomes into agro-ecosystems, we demonstrate a scalable approach to reconcile crop productivity with soil biodiversity conservation. These results demonstrate the potentiality of these endophytic microbes in sustainable agriculture, environmental management, and microbial biotechnology. Further studies on their metabolic pathways may expand their applications in bioremediation and plant-microbe interactions.